Development of a quality control manual for pork nuggets - Tabun, Aileen Pamplona; Rivera Lourdes S. (1994.)
The quality control manual for pork nuggets was developed to provide the Bureau of Animal Industries (BAI) with a complete reference guide to help them enable to produce nuggets of consistent good quality. The development of a manual was subdivided into four phases. The first phase aimed to compare the BAI nuggets with a similar product already available in the market. The results helped determine the areas of improvement with regards to the product as well as to its degree of acceptability as against the control. The second phase was the improvement and standardization of both the product and its production process at laboratory scale. In the next phase, three trial pilot scale productions were conducted to check if the standardization steps taken were both correct and sufficient to ensure good quality each time. And, in the final phase, the actual quality control manual was created, based on all the data gathered from the previous phases.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Pork -- Handbooks, manuals, etc; Pork -- Quality control